2018
DOI: 10.1186/s41043-018-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ knowledge and attitudes about childhood diarrhea among refugee and host communities in Gambella Region, Ethiopia

Abstract: BackgroundMaternal knowledge, attitudes, and practices related to hygiene, breastfeeding, sanitary food preparation, and appropriate weaning practices are potentially important determinants in the occurrence of diarrhea in children. However, few studies have been carried out about the knowledge and attitudes about childhood diarrhea among parents in refugee camps and host communities.ObjectiveThis study aims at assessing the caregivers’ knowledge and attitudes regarding acute diarrhea in under-five children am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
7
1
1
Order By: Relevance
“…Majority of the respondents in this study had good attitude similar findings were reported by Gundluru et al [ 39 ]. This was however contrary to some studies which reported unfavorable caretakers’ attitude [ 14 , 40 ]. Patients get all prescribed drugs from the facility as expected since most of the care givers sought care/treatment at public health facilities that offer free services.…”
Section: Discussioncontrasting
confidence: 97%
“…Majority of the respondents in this study had good attitude similar findings were reported by Gundluru et al [ 39 ]. This was however contrary to some studies which reported unfavorable caretakers’ attitude [ 14 , 40 ]. Patients get all prescribed drugs from the facility as expected since most of the care givers sought care/treatment at public health facilities that offer free services.…”
Section: Discussioncontrasting
confidence: 97%
“…However, many studies have indicated that these implementations are costly to the provider and vulnerable to network conditions. The text-based nature of these apps further does little to support low-literacy users, and bulk SMS text messages are not sufficient to enable and maintain relationships between health professionals and their patients [ 159 ]. Finally, the broadcast nature of these messages creates an opportunity for providers to celebrate the number of subscriptions, instead of the number of messages read and interacted with.…”
Section: Discussionmentioning
confidence: 99%
“…[Social sciences applied to health researcher] Usability studies and considerations are also underrepresented, with 3 articles explicitly addressing the usability of technology tools aimed at MCH. The literature highlights usability considerations in areas such as heart failure [100], digital and maternal storytelling [159], and preeclampsia triage [101]. HCI in health research accounts for all articles measuring usability.…”
Section: And My Work Focuses On Children Is On Their Eating Behaviour...mentioning
confidence: 99%
“…With 90% condence interval and margin of error as 5%, with previous proportion of 72%, the anticipated sample size was calculated to be 271. 9 A convenient sampling technique was used to select the participants for this study. Mothers of under ve years age children who were admitted in pediatric ward due to diarrhea were included in the study.…”
Section: Methodsmentioning
confidence: 99%